The abolition of collagen gene expression in SV40-transformed fibroblasts is associated with trans-acting factor switching. - Parker, M I (1992)
The goal of this study was to determine whether alpha 2(1) procollagen gene expression is modulated by positive or negative trans-acting DNA-binding proteins. Previous studies have shown that a clone of SV40-transformed WI-38 fibroblasts (SVWI-38) does not produce any alpha 2(1) procollagen mRNA (Parker et al (1989), J. Biol Chem. 264, 7147-7152). In order to elucidate the mechanism(s) responsible for such inactivation, we have examined the activity of a transfected wild type COL1A2 promoter in SVWI-38 cells. A set of 5' promoter deletions was linked to the chloramphenicol acetyltransferase (CAT) gene and transfected into SVWI-38 and other cell lines expression type I collagen. The resulting CAT assays confirmed the importance of several upstream regions for promoter activity and documented the decreased transcriptional activity from an exogenous COL1A2 promoter in the SVWI-38 cell line. Competition experiments with an excess of COL1A2 promoter DNA fragment and a constant amount of COL1A2/CAT construct displayed a linear relationship between excess COL1A2 fragment and CAT activity in SVWI-38 cells, suggesting the involvement of a titratable negative effector. Electrophoretic mobility shift assays revealed the presence of a specific DNA-protein complex which was present in SVWI-38 cells and almost absent in control fibroblasts. Methylation interference analysis mapped the region of binding of this factor between nucleotides -80 and -72, relative to the transcription start site. Thus the data presented provide strong evidence for the existence of a negative trans-acting factor that may play a role in the repression of COL1A2 expression in SVWI-38 fibroblasts.